Pesantren and Scholarly Works: A Literacy Ethos as the Brand Culture of Pesantren - Arwani, Ragil (Journal of Pesantren and Diniyah Studies, 2025)
This study examines pesantren branding as a cultural strategy for building a brand culture rooted in Islamic scholarly traditions, an area that remains relatively underexplored in the educational branding literature. This study aims to analyze how branding practices are constructed, interpreted, and institutionalized in the context of pesantren. The research uses a qualitative case study design at Pondok Pesantren Hidayatut Thullab Kediri. Data were collected through in-depth interviews, participant observation, and document analysis, and then analyzed inductively and thematically. The results show that pesantren branding is developed through the practice of scientific writing, which serves as an institutional identity and collective culture. This branding is built through three main aspects: the scientific leadership initiative initiated by the (late) KH. Yasin Asmuni, institutional marketing support, and the formation of cadres based on mastery of scientific works. This study also identifies three models of pesantren branding: brand communication grounded in scientific narratives, brand expression through academic content, and brand management that adapts to cultural changes. These findings enrich educational branding studies by offering a branding model grounded in the intellectual traditions and scientific culture of pesantren.